2016
DOI: 10.1021/acs.orglett.6b01435
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Chiral Amido-Thiourea Catalysts Enables Improved Activity and Enantioselectivity

Abstract: While aryl pyrrolidinoamido thioureas derived from α-amino acids are effective catalysts in a number of asymmetric transformations, they exist as mixtures of slowly interconverting amide rotamers. Herein, the compromising role of amide bond isomerism is analyzed experimentally and computationally. A modified catalyst structure that exists almost exclusively as a single amide rotamer is introduced. This modification is shown to result in improved reactivity and enantioselectivity by minimizing competing reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Accordingly, the 2-arylpyrrolidine was alkylated to constrain the amide in exclusively the ( Z )-rotameric form, thereby positioning the aryl group proximal to the H-bond donor active site (see Supporting Information for NMR and crystallographic characterization). 36 Catalysts bearing this constrained amide ( 4 , 5 , and 6 ) proved reactive and displayed improved enantioselectivity (entries 3–7). Complementary tuning of the arylpyrrole moiety revealed that catalysts 5b and 6b enable access to product 2a in high enantiomeric excess (entries 5 and 7), even with reduced catalyst loading (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the 2-arylpyrrolidine was alkylated to constrain the amide in exclusively the ( Z )-rotameric form, thereby positioning the aryl group proximal to the H-bond donor active site (see Supporting Information for NMR and crystallographic characterization). 36 Catalysts bearing this constrained amide ( 4 , 5 , and 6 ) proved reactive and displayed improved enantioselectivity (entries 3–7). Complementary tuning of the arylpyrrole moiety revealed that catalysts 5b and 6b enable access to product 2a in high enantiomeric excess (entries 5 and 7), even with reduced catalyst loading (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Although preliminary DFT analysis did not distinguish whether catalyst activation proceeds by a 4H-or a 2H-Cl − -binding geometry, i.e., via I or II (Figure 48), in the solid-state, a 4H-geometry was observed, a fact, which guided the choices of structural changes [90,91]. A methyl substituent, shown previously to minimize competing reaction pathways and improve reactivity and the ees, was introduced [94]. The bisthioureas were also linked in a way that disfavored aggregation while still resembling the structures of the untethered monomers.…”
Section: Miscellaneous Reactions Involving Anion-binding Catalysismentioning
confidence: 97%
“…These findings proved to be decisive in the development of new and more efficient anion-binding catalysts. By introducing a methyl group (R = Me) into the pyrrolidine moiety of the initial catalyst design, the amide is conformationally constricted to the ( Z )-rotamer [ 75 ]. Consequently, improved enantioselectivity and catalytic efficiency could be observed (>95% conv., 97% ee).…”
Section: Reviewmentioning
confidence: 99%